2019
DOI: 10.1002/app.47692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of atactic polypropylene: Propylene polymerization reactions with TiCl4–Al(C2H5)2Cl/Mg(C4H9)2 catalyst

Abstract: The Ziegler catalyst, a combination of TiCl4 and Al(C2H5)2Cl, is a very poor catalyst for propylene polymerization. However, the addition of Mg(C4H9)2 to the Ziegler catalyst at a [Mg]:[Al] molar ratio < 0.5 leads to the formation of a potent catalyst system for homopolymerization of propylene. Polymers produced with the TiCl4–Al(C2H5)2Cl/Mg(C4H9)2 catalyst are mostly atactic and amorphous, their minor partially crystalline isotactic components constitute merely 5–10% of the combined polymer material. Principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…30 Increasing the MAO loading resulted in increased polymerisation activities up to a maximum value at 2500 equivalents of 12 000 and 11 000 kg PP mol Ti −1 h −1 bar −1 for 2 sMAO and 2 respectively. This activity compares well with some of the most active polypropylene catalysts in literature: the TiCl 4 –Al/Mg system reported by Rishina et al and the fluorenyl zirconocene reported by Resconi et al have activities of 22 000 and 29 000 kg PP mol −1 h −1 respectively when used in liquid propylene, 7,53 a far greater concentration of monomer than the 2 bar pressure used in this work. 54 Runs were attempted using 2 and other alkyl aluminium cocatalysts – TMA, TEA, and TIBA – in place of MAO, but negligible activity was recorded in these cases.…”
Section: Resultssupporting
confidence: 89%
“…30 Increasing the MAO loading resulted in increased polymerisation activities up to a maximum value at 2500 equivalents of 12 000 and 11 000 kg PP mol Ti −1 h −1 bar −1 for 2 sMAO and 2 respectively. This activity compares well with some of the most active polypropylene catalysts in literature: the TiCl 4 –Al/Mg system reported by Rishina et al and the fluorenyl zirconocene reported by Resconi et al have activities of 22 000 and 29 000 kg PP mol −1 h −1 respectively when used in liquid propylene, 7,53 a far greater concentration of monomer than the 2 bar pressure used in this work. 54 Runs were attempted using 2 and other alkyl aluminium cocatalysts – TMA, TEA, and TIBA – in place of MAO, but negligible activity was recorded in these cases.…”
Section: Resultssupporting
confidence: 89%
“…These different catalysts produce different microstructures of syndiotactic PP with different crystallization behavior and properties through different polymerization mechanisms. Atactic polypropylene can also be produced selectively using metallocene catalysts, atactic polypropylene produced this way has a considerably higher molecular weight [62,63].…”
Section: Polypropylene Materialsmentioning
confidence: 99%
“…We found earlier that combinations of chloro‐organoaluminium compounds AlR 2 Cl and organomagnesium compounds MgR′ 2 , when used at an [Al]:[Mg] molar ratio above 2, are universal cocatalysts for converting various types of transition metal compounds into alkene polymerization catalysts, including TiCl 4 , 9,10 common heterogeneous and supported Ti‐based catalysts, 11 metallocene complexes 12 and many post‐metallocene complexes 11–17 …”
Section: Introductionmentioning
confidence: 99%